(untitled) (Security Dialogues, 2025)
The North Atlantic Treaty Organization (NATO), comprised of 32 member states from North America and Europe, represents the largest military and political alliance of today. Membership in NATO is widely accepted as a guarantee of security, but it has been a subject of political conflict in Bosnia and Herzegovina for an extended period, as well as in other countries in the region. Currently, all Western Balkan countries (Albania, North Macedonia, and Montenegro) except Bosnia and Herzegovina and the Republic of Serbia are full members of NATO. Under the guise of military neutrality, the Republic of Serbia rejects the desire for full NATO membership, citing the NATO bombing of the then Federal Republic of Yugoslavia in 1999 as a key argument against joining. Bosnia and Herzegovina initially had unanimous support for full NATO membership after the signing of the General Framework Agreement for Peace in Bosnia and Herzegovina, but over time, this support weakened and transformed into open opposition from representatives of the Republika Srpska entity. The lack of a pragmatic and thorough assessment of the interests of joining NATO, considering regional and global developments, Russian influence on the Balkans and the fact that there is a new reordering of the fragmented order in which military-political neutrality loses its meaning, further complicates the integration process in Bosnia and Herzegovina. Analyze of the impact of Bosnia and Herzegovina’s membership in NATO and its consequences are in focus of this paper.